Desenvolvimento de protótipo de robô móvel com rodas diferencial para implementação de estratégias de controle de movimento: aplicação da técnica realimentação linearizante - Wilhelm, Mateus Luiz (2020)
The mathematical models of Wheeled Mobile Robots (WMRs) are characterized as Nonlinear Multiple-Input Multiple-Output (MIMO) systems and, depending on the configuration of the robot wheels, it may have nonholonomic constraints. The motion control of the robot, which aims to determine the forces/torques necessary to move the WMR, is developed considering those characteristics of the WMRs, so that the robot performs tasks with the desired performance. The mathematical model of an WMR contains the kinematic equation of its structure and it can also include its dynamic equation, which includes mass and moment of inertia into the mathematical model of the vehicle. One of the approaches used in motion control, and applied in several works, is the feedback linearization, which consists of transforming a nonlinear system, fully or partially, into a linear system through nonliner state feedback. In this work a prototype with open architecture of the Differential Wheeled Mobile Robot (DWMR) is developed, which consists of a mechatronic system, for the implementation and testing of motion control systems. In addition, techniques are applied for the transformation of control signals into signals suitable for the prototype actuators, as well as for obtaining of the state variables using information from the prototype sensors. As one of the contributions of the work, a technique is developed in which, different from most works in the area, the obtainment of the duty cycle related to the PWM signal, used to regulate the voltage applied to the prototype actuators through H-bridge drivers, is performed in function the calculated voltage in the actuators and the angular speed of the wheels measured by sensors. In this work, the Raspberry Pi is adopted as the prototype processing unit and the simulations and practical experiments are performed using Matlab/Simulink tools, which support integration with Raspberry. In order to evaluate the prototype, two control strategies are selected to be tested, both based on feedback linearization. The first control system considers only the DWMR kinematic model and the second, on the other hand, considers both kinematic and dynamic models. The exposed control problem con sists of trajectory tracking. The simulations and tests with the prototype are performed for two different trajectories. The results obtained with the prototype are satisfactory because they have low tracking errors for both control systems implemented. The DWMR built, even in a first version and composed, in part, of common devices and algorithms, proves to be quite viable for the implementation and testing of motion control strategies of WMRs.